Ecofloristics and Conservation Status of Sacred Groves-A Comparative Study from Bankura District, West Bengal - Nayak, Atanu; Bhakat, Ram Kumar; Pandit, Prasanta Kumar (Indian Forester, 2023)
Sacred groves are tree clusters protected on socio-religious grounds since ancient times and often dedicated to certain regional deities. This paper highlights the comparative account of eight (8) isolated sacred groves, situated in eight (8) administrative blocks of Bankura district, West Bengal. These groves conserve 190 species of angiosperms including some economically and medicinally important plant species, of which a significant portion (28.42%) is tree in nature, though herbs constitute the majority (39.4%). Although the size of the groves is different as so their species richness is, but there lying a strong positive correlation (r=0.93, p<0.001) between them. Distribution pattern analysis of the flora reveals that majority of the plants (82 sp.) fall into the frequency class B followed by frequency class ‘A’ (74 sp.). Besides, these groves in-house three near threatened (NT) and one vulnerable (VU) plant species according to the IUCN Red List 2022-2. Site disturbance score analysis of the groves reveals that maximum numbers of studied groves (5) fall into the category B, whereas invasion and grazing are the main two factors affecting the site scores. While enumerating the invasive alien species (IAS), a total number of 48 species were documented. Moreover, it is also found that there is strong negative correlation (r=-0.91, p<0.001) between species richness (S) of a sacred grove and the percentage of IAS found within. The nativity of the invaders was also worked out. This study thus recommends to manage sacred groves by classifying them on the basis of their site score and special emphasis should be given to restore the severely effected such groves as they are not only the adobe of regional biodiversity but also the institutions of our cultural heritage.